(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Hookah smoking is increasing worldwide. It is estimated the worldwide prevalence of daily hookah smoking is 100 million. The aim of this study was to compare hookah smoking prevalence in Islamic Azad University medical students in the city of Ardabil between 2009 and 2014. Method: Of 2956 Islamic Azad University medical students, Ardabil branch, almost 25% of students 737 students (226 males vs. 511 females; 436 subjects at 2009 vs. 301 subjects at 2014) were randomly selected to participate in this survey. An anonymous self-administered questionnaire was used after verbal informed consent according to the Review Committee of Ardabil Branch Islamic Azad University Medicine School approved protocol. A cluster sampling technique was used. The questions focused on gender, hookah smoking status, and students’ replies for the following issues: (1) Kind of hookah (2) Frequency of smoking (3) Motivation of hookah use (4) Place of smoking use (5) and Second-hand exposure to hookah. Results: Hookah use showed significant decrease in male students compared with five years ago (P<0.05). Frequency of molasses (tobacco with sweetened fruit flavors and mild aromatic smoke) use has significantly enhanced among both genders in 2014 compared with 2009 (P<0.05). Furthermore, second-hand exposure to hookah was significantly higher among both nonsmoker genders at 2014 compared with 2009 (32.7% at 2014 vs. 13.2% at 2009). Conclusion: Unfortunately, in spite of knowledge promotion among medicine school students in recent years, hookah use is still prevalent among medical students. Molasses use has significantly increased and second hand exposure to tobacco has escalated since 2009.